An Investigation of The Hijra Process Among Young Generation - Widyaningsih, Rindha; Riswan , Yulianingsih; Aprianto, Naerul Edwin Kiky; Maulana, Zidan Abid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to examine the process of hijra among young people. The study was in the BARLINGMASCAKEB area (Banjarnegara, Purbalingga, Banyumas, and Cilacap). The study subjects were carried out by purposive sampling individuals who hijra online or offline (outside the network). Data collection techniques are carried out by structured interviews with research subjects and strengthened by a literature review and data analysis techniques by reducing data, classifying data, interpreting, and drawing conclusions. The data obtained are presented as narrative text, tables, and charts. Testing the validity of the data is carried out by the data triangulation method. The results showed that the hijra process consists of two types: self-taught and through institutions. Most hijra practitioners who learn self-taught are accomplished online, while the rest learn offline and a combination of online and offline. Hijra perpetrators carry out a face-to-face direct process with the ustadz / ustadzah and the hijra community while actively accessing hijra and religious content through online recitation or joining social media channels. The second process in hijra is studying directly at religious institutions following the manhaj. They study religion at religious institutions to get precise knowledge and be more methodical to avoid misunderstanding religious teachings.